Multiple case studies of the interiors of selected police community precincts in Quezon City - Agustin, Nathaniel John C.
The study aimed to analyze the existing interior spaces of selected Police Community Precincts (PCPs) in Quezon City. The research objective is to provide initial design considerations based on the roles of the PCPs and through acquired data of the interior condition of the structure. The study utilized convenience sampling as the PCPs and police officers who served as respondents for the interviews were pre-selected by the Office of the District Police Community Relations Division of the Quezon City Police District were chosen to adhere to the rules of the agency. Patterns of similarities in the interior elements of the PCPs were noted from across the six (6) precincts from data collection strategies such as site observation, photo documentation, site measurement, and focus interviews. Instruments included an interview guide, a voice recorder, a field notebook and a high-resolution camera. Data affirmed no design reference was utilized for all six community precincts in Quezon City although interior elements such as the operational and service areas, equipment, and furniture pieces that were found consistently present across the PCPs. The data were tabulated and examined through content analysis and coding. The six (6) police community precincts were not built according to the function it was expected to perform. Further analysis also showed that while the basic functions (deployment, administrative tasks and community relations) of PCPs are performed in the space, addressing the human needs of all the officers are least prioritized. Funding and the lack of space standardization emerged as issues needed to be addressed. The recommendations from the study include the development of a standard design considerations that includes the room segregation for operational and service areas, furniture, fixture and equipment list and use of multifunctional pieces of furniture. It is suggested that gender-neutral spaces be included in the design considerations.